2013
DOI: 10.3390/rs5010127
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Human Controls of Ecosystem Functional Diversity in Temperate South America

Abstract: Abstract:The regional controls of biodiversity patterns have been traditionally evaluated using structural and compositional components at the species level, but evaluation of the functional component at the ecosystem level is still scarce. During the last decades, the role of ecosystem functioning in management and conservation has increased. Our aim was to use satellite-derived Ecosystem Functional Types (EFTs, patches of the land-surface with similar carbon gain dynamics) to characterize the regional patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 86 publications
(102 reference statements)
4
70
0
Order By: Relevance
“…For example, EFTs in high latitudes were shown to be controlled by temperature whereas EFTs in the arid and semi-arid areas were associated with water constraints of vegetation growth. We found a good correspondence of the global spatial pattern of these constraints within the EFTs and results of other authors on patterns of ecosystem-climate relationships (e.g., [29,32,44]). Nemani et al [29] showed that water availability strongly limits vegetation growth over 40% of Earth's vegetated surface, whereas temperature limits growth over 33% and radiation over 27%.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…For example, EFTs in high latitudes were shown to be controlled by temperature whereas EFTs in the arid and semi-arid areas were associated with water constraints of vegetation growth. We found a good correspondence of the global spatial pattern of these constraints within the EFTs and results of other authors on patterns of ecosystem-climate relationships (e.g., [29,32,44]). Nemani et al [29] showed that water availability strongly limits vegetation growth over 40% of Earth's vegetated surface, whereas temperature limits growth over 33% and radiation over 27%.…”
Section: Discussionsupporting
confidence: 57%
“…Recent decades have seen an increasing need for information on ecosystem functioning to evaluate the human impact on the environment [32]. A baseline characterization of ecosystem functioning is to be based on an up-to-date, effective and repeatable indicator system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations